Expressiveness and frequency differences of hip joint tissues pathomorphological changes in diseases complicated by femoroacetabular impingement syndrome - V. V. Grigorovsky; V. V. Filipchuk; M. S. Kabatsiy (Zaporozhye State Medical University, 2013)
Preface. Last years the increasing value in pathogenesis of hip joint osteoarthrosis (ОА) both in adult patients and in children and teenagers is attached to articular surfaces congruence violation of the femoral head and acetabulum that is formed by articular cartilage and labrum, the last one by head movements in the maximum hip flexion and adduction enters in femoroacetabular impingement (FAI) with edge of the head and allied site of the neck and is mechanically damaged. Purpose of the work. To establish hip joint tissues pathomorphological changes, to which FAI syndrome leads, and on the basis of graded expressiveness quantification of pathological changes to define differences of their occurrence frequency in groups of patients in some diseases with affected hip joint. Materials and research methods. 65 biopsies of hip joint tissues: proximal femoral epimetaphysis, acetabulum, acetabular lip and joint capsule -from patients with aseptic femoral head necrosis (АNFH) and juvenile slipped femoral capital epiphysis (JSFCE). After study of qualitative features of hip joint tissues injury, some graded morphological indices characterizing conditions of affected joints, as occurrence frequencies of pathological changes of certain gradation, and also their comparison in groups of monitoring with calculation of their distinctions significance, were estimated. Results and their discussion. Clinical-pathomorphological research has revealed the various pathological changes shown by signs of discirculatory, chronic dystrophic-destructive and inflammatory processes in tissues of the femoral head, neck, acetabulum and joint capsule. FAI, causing secondary dystrophic-destructive changes in hip joint tissues, has different rates of development in various primary pathology: in JSCFE anatomic conditions of FAI develop faster, in АNFH - more slowly in the dynamics of secondary changes, the last ones do not differ statistically in various nosologies on rates of the development of symptoms leading to the necessity of correcting operations on the joint. Degrees of "femoral head articular surface deformation" in various nosologies essentially differ on frequency of occurrence of cases with certain expressiveness: if in patients with JSFCE only low degree of femoral head deformation occurs, in АNFH cases with high degree of expressiveness comprise over one third, that is connected, probably, with features of the basic pathological processes in femoral head spongiosa in this disease. Occurrence frequency of nonspecific synovitis cases of certain activity degree depends from primary nosology which has become complicated by FAI: among patients with АNFH synovitis of average or high degree was found significantly more frequent, than among patients with JSFCE in whom cases of low activity synovitis prevail. Conclusions. In the present work comparative research of all hip joint tissues was performed for the first time on rather big clinical-morphological material, with application of graded indices and the frequency analysis, degrees of pathological changes expressiveness are defined and distinctions of frequencies of occurrence in groups of comparison of patients with АNFH and JSFCE, complicated by FAI, were established.